Schroederichthys bivius, Narrowmouth Catshark - Dulvy, N. K. (2020)
The Narrowmouth Catshark (Schroederichthys bivius) is a small (to 82 cm total Length) catshark that occurs in the Southeast Pacific and Southwest Atlantic from Valdivia, Chile, south around Cape Horn and north to southern Brazil. It is demersal on the continental shelf and upper slope at depths of 12-359 m (mostly <130 m). It is occasionally caught as bycatch of industrial and artisanal trawlers in Chile, Uruguay, Argentina, and the Falkland Islands (Malvinas). It is not typically utilized and is usually discarded dead. Overall, this catshark is caught throughout most of its range in small numbers. Its small size and presumably productive life history, combined with a lack of evidence of a population reduction, indicates that it is likely able to withstand limited exposure to fishing pressure. The population is suspected to be stable, therefore, the Narrowmouth Catshark is assessed as Least Concern.